National Histories and Ethnic History in Canada - Perin, Roberto (Cahiers de recherche sociologique, 1993)
SummaryNational history is out of fashion in Canada. Since the 1960s the constitutional crisis which has challenged the unitary character of the Canadian State has had a profound impact on its historiography. It is in this troubled context that social history emerged. In seeking to reconstitute the internal history of social groups, it broke the "national" consensus that had been created around not only the interpretations, but the periodicity of traditional history. The question now arises as to whether national history still exists as a category. If so, how many national histories does Canada have? Where do the First Nations and immigrant groups fit into to this (these) national history (histories), or do they have national histories of their own?